2011
DOI: 10.1073/pnas.1102943108
|View full text |Cite
|
Sign up to set email alerts
|

HIV DNA is heavily uracilated, which protects it from autointegration

Abstract: Human immune cells infected by HIV naturally contain high uracil content, and HIV reverse transcriptase (RT) does not distinguish between dUTP and dTTP. Many DNA viruses and retroviruses encode a dUTPase or uracil-DNA glycosylase (UNG) to counteract uracil incorporation. However, although HIV virions are thought to contain cellular UNG2, replication of HIV produced in cells lacking UNG activity does not appear to be impaired. Here we show that HIV reverse transcripts generated in primary human immune cells are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 48 publications
1
63
0
2
Order By: Relevance
“…As inferred from HIV-1 infections in nondividing cells (25), we found that HIV-1 readily incorporates dUTP during reverse transcription, and dUTP incorporation only produced a small kinetic delay in cDNA synthesis with no effect on the ultimate levels of viral cDNA. However, dUTP incorporation resulted in a sevenfold reduction in viral integration, and this reduction was completely dependent on the removal of uracils by nuclear hUNG2, leading to degradation of the viral genome.…”
Section: Significancementioning
confidence: 65%
See 4 more Smart Citations
“…As inferred from HIV-1 infections in nondividing cells (25), we found that HIV-1 readily incorporates dUTP during reverse transcription, and dUTP incorporation only produced a small kinetic delay in cDNA synthesis with no effect on the ultimate levels of viral cDNA. However, dUTP incorporation resulted in a sevenfold reduction in viral integration, and this reduction was completely dependent on the removal of uracils by nuclear hUNG2, leading to degradation of the viral genome.…”
Section: Significancementioning
confidence: 65%
“…3D). In fact, Yan et al (25) have proposed that uracilation of viral cDNA aids in integration by discouraging the competing and nonproductive autointegration reaction. Our results now uncover an additional consideration where nuclear hUNG2, if present at high enough levels, would efficiently degrade uracilated DNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations